History backfires: Reminders of past injustices against women undermine support for workplace policies promoting women - Hideg, Ivona; Wilson, Anne E. (Organizational behavior and human decision processes, 2020)
•Reminders of past injustice toward women undermine men’s support for an EE policy.•Undermined support is due to men’s denial of current gender discrimination.•Reminders of past injustice toward women do not influence women’s reactions to EE.•Information about women’s advancement mitigate men’s negative reactions to EE.•Men’s undermined support for EE is further mediated by lower collective self-esteem. Public discourse on current inequalities often invokes past injustice endured by minorities. This rhetoric also sometimes underlies contemporary equality policies. Drawing on social identity theory and the employment equity literature, we suggest that reminding people about past injustice against a disadvantaged group (e.g., women) can invoke social identity threat among advantaged group members (e.g., men) and undermine support for employment equity (EE) policies by fostering the belief that inequality no longer exists. We find support for our hypotheses in four studies examining Canadian (three studies) and American (one study) EE policies. Overall, we found that reminders of past injustice toward women undermined men’s support for an EE policy promoting women by heightening their denial of current gender discrimination. Supporting a social identity account, men’s responses were mediated by collective self-esteem, and were attenuated when threat was mitigated. Reminders of past injustice did not influence women’s support for the EE policy.